Natural phenolics in the prevention of UV-induced skin damage. A review - Svobodova, Alena; Psotova, Jitka; Walterova, Daniela (Biomedical papers, 2003)
UV skin exposure induces extensive generation of reactive oxygen species (ROS). These can react with DNA, proteins, fatty acids and saccharides causing oxidative damage. Such injuries result in a number of harmful effects: disturbed cell metabolism, morphological and ultrastructural changes, attack on the regulation pathways and, alterations in the differentiation, proliferation and apoptosis of skin cells. These processes can lead to photoaging and skin cancer development. One approach to protecting human skin against the harmful effects of UV irradiation is to use antioxidants as photoprotectives. In recent years naturally occurring herbal compounds such as phenolic acids, flavonoids, and high molecular weight polyphenols have gained considerable attention as beneficial protective agents. In this review, we strive to summarize the findings of studies performed to date, regarding the photoprotective effects of plant phenolics on the skin damage induced by UV radiation.
Keywords: UV radiation / Keratinocytes / Fibroblasts / ROS / Photoprotection / Polyphenol / Plant extract